Advance care planning for people living with dementia: An umbrella review of effectiveness and experiences. (July 2020) - Wendrich-van Dael, Annelien; Bunn, Frances; Lynch, Jennifer; Pivodic, Lara; Van den Block, Lieve; Goodman, Claire
Abstract: Background: End of life care is often inadequate for people with dementia. Advanced care planning (ACP) has the potential to improve outcomes for people with dementia. The aim of this review is to establish the strength of the evidence and provide decision makers with a clear understanding of what is known about ACP for people living with dementia. Design: Evidence synthesis including systematic reviews and primary studies. PROSPERO registration: CRD42018107718. Data sources: PubMed, CINAHL Plus, SCOPUS, Social Care Online and Cochrane Library were searched (July 2018). No year limit applied. To be included, reviews had to evaluate effectiveness of ACP for people with dementia or report on views and experiences of ACP from the perspective of people with dementia, carers, or health and care professionals. Additional searches (September 2018) were conducted to identify recent primary studies not included in the reviews. Review methods: Data extraction was undertaken by one reviewer and checked by a second. Methodological quality was assessed using AMSTAR-2 and Joanna Briggs Institute instruments by two authors independently. Outcomes were categorized and tabulated to assess effectiveness. Qualitative data was analysed using thematic synthesis. Results: Nineteen reviews (163 unique studies) and 11 primary articles with a range of advance care planning definitions and of variable quality were included. Advance care planning was associated with decreased hospitalizations, increased concordance between care received and prior wishes and increased completion of advance care planning documents but quality of primary research was variable. Views of ACP for people with dementia can be clustered around six themes; 1) timing and tailoring, 2) willingness to engage, 3) roles and responsibilities of healthcare professionals, 4) relationships, 5) training and 6) resources needed. Diminishing decision-making capacity over time is a key overarching feature. Conclusions: Advance care planning is acceptable for people with dementia and their carers and is associated with improved outcomes. Guidelines on which outcomes and which definition to use are necessary, as is research to test different approaches to ACP. Education on topics related to diminishing decision-making capacity is key to optimize advance care planning for people with dementia and their carers.